Unveiling the mechanism of electron transfer facilitated regeneration of active Fe2+ by nano-dispersed iron/graphene catalyst for phenol removal. Issue 43 (22nd May 2017) - Wang, Penglei; Zhou, Xin; Zhang, Yagang; Yang, Liping; Zhi, Keke; Wang, Lulu; Zhang, Letao; Guo, Xinfeng
Abstract : Unveiling the mechanism of electron transfer-facilitated regeneration of active Fe 2+ by nano-dispersed iron/graphene catalyst for phenol removal. Abstract : Nano-dispersed Fe 0 and Fe3 O4 on reduced graphene oxide (Fe 0 /Fe3 O4 -RGO) was prepared and characterized. The prepared Fe 0 /Fe3 O4 -RGO was used as a magnetically separable Fenton-like catalyst and showed superior catalytic activity compared to Fe3 O4 -RGO and Fe3 O4 as well as other Fenton-like catalysts for the removal of phenol. The Fe 0 /Fe3 O4 -RGO achieved 100% removal efficiency for phenol within 30 min. Free radical inhibition experiments and Electron Paramagnetic Resonance (EPR) showed that the main reactive species was ˙OH rather than Fe IV . High resolution TEM results revealed that nanoscale Fe 0 and Fe3 O4 were uniformly dispersed and distributed on RGO without agglomeration, furnishing more active sites. The catalyst featured a unique mechanism of electron transfer-facilitated regeneration of active Fe 2+ by nano-dispersed iron/graphene. RGO served as an effective mediator to facilitate the electron transfer from Fe 0 to Fe 3+ for the regeneration of Fe 2+, which was critical in the catalytic process. This electron transfer-facilitated regeneration of active Fe 2+ resulted in a reusable catalyst with high catalytic activity for the removal of phenol. The nano-dispersed Fe 0 /Fe3 O4 -RGO could be easily separated and recovered by magnetic field. The Fe 0 /Fe3 O4 -RGO catalyst was reusable and the removal efficiency of phenol after 5 catalytic cycles was as high as 93%. The Fe 0 /Fe3 O4 -RGO could be an effective Fenton-like catalyst for the treatment of waste water containing refractory phenol and phenol type pollutants.